"I Was in Prison and You Visited Me": A Sacramental Approach to Rehabilitative and Restorative Criminal Justice - Amy Levad - Journal of the Society of Christian Ethics (Philosophy Documentation Center) - Levad, Amy (Journal of the Society of Christian Ethics, 2011)
ROMAN CATHOLIC ETHICISTS AND THEOLOGIANS HAVE REMAINED RELAtively silent about crises in US criminal justice systems, with two exceptions. The US Conference of Catholic Bishops published a document in 2000 calling for rehabilitative and restorative approaches to crime. Historian Andrew Skotnicki has criticized the bishops for ignoring traditional Catholic models of punishment—monastic and ecclesiastical prisons. This essay challenges Skotnicki and bolsters the bishops' argument by proposing that the sacraments, especially the Eucharist and Penance, provide a stronger basis in Catholicism for responding to crime and the crises in US criminal justice systems in ways that foster rehabilitation and restore justice while also reforming broken systems and promoting social justice.